2021
DOI: 10.1002/advs.202100997
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Energy Metabolism in Ferroptosis Regulation of Tumor Cells

Abstract: Ferroptosis is a new form of regulated cell death, which is characterized by the iron-dependent accumulation of lethal lipid peroxides and involved in many critical diseases. Recent reports revealed that cellular energy metabolism activities such as glycolysis, pentose phosphate pathway (PPP), and tricarboxylic acid cycle are involved in the regulation of key ferroptosis markers such as reduced nicotinamide adenine dinucleotide phosphate (NADPH), glutathione (GSH), and reactive oxygen species (ROS), therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 147 publications
0
85
0
Order By: Relevance
“…Cell death is caused by a variety of mechanisms. Cell death modes include autophagy, pyroptosis, Wallerian degeneration, excitotoxicity, and ferroptosis [ 6 8 ]. Ferroptosis is a nonapoptotic cell death mode, which is significantly different from other programmed cell death [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell death is caused by a variety of mechanisms. Cell death modes include autophagy, pyroptosis, Wallerian degeneration, excitotoxicity, and ferroptosis [ 6 8 ]. Ferroptosis is a nonapoptotic cell death mode, which is significantly different from other programmed cell death [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that VDAC3 could affect cell ferroptosis by regulating the mitochondrial entry and exit of iron ions 19 , 20 , 45 . Excessive iron accumulation could result in ROS production through the Fenton reaction and then cause ferroptosis 46 , 47 . Our results showed that when BDNF-AS was overexpressed, the VDAC3 protein expression level increased.…”
Section: Discussionmentioning
confidence: 99%
“…As the site for intracellular oxidative respiration, mitochondrion is a major source of ROS. By promoting mitochondrial respiration, the ferroptosis promoter erastin can increase the production of ROS and thus promote ferroptosis by enhancing mitochondrial respiration ( Yao et al, 2021b ). Combined with the results of the above causal inference, we believe that ferroptosis leads to the low expression of GPX4, which promotes the accumulation of ROS and reduces the inhibition of CDH2 expression, thereby promoting the occurrence of EMT.…”
Section: Resultsmentioning
confidence: 99%